Individual Granting of Academic Degrees Model: Case of MGIMO-University - M. I. Inozemtsev (Высшее образование в России)
August 23, 2019 marks two years from when approval was given to those top scientific and educational organizations that were entitled to grant individual academic degrees and diplomas. Today it is not only Moscow State University and St Petersburg State University but other 23 universities that are involved in the pilot project of implementing the new governmental model of scientific accreditation. MGIMO University was one of the first universities that created and implemented its own model. For the last two years there have been 80 research paper defences in 9 scientific fields. In his interview, Maxim Inozemtsev, Head of Dissertation Council Department, revealed the main features of the model for individually granting academic degrees, as well as the challenges, trends and innovation in the scientific accreditation procedure.